The Influence of Toxic Parenting on Bullying Behavior - Budi, Mustika; Nuansa, Diaz Aviary (Journal of Counseling and Educational Research, 2024)
The aim of this research is to find out whether there is an influence of toxic parenting on bullying behavior and aims to see a picture of toxic parenting on bullying behavior. The method used in this research uses a quantitative approach. The population and sample in this research were 185 students at SMAN 93 Jakarta. Data were analyzed using SPSS version 27 software with linear regression techniques. The findings in this research are that there is a significant influence of toxic parenting (X) on bullying behavior (Y), seen from the contribution given by toxic parenting of 20.1% to bullying behavior. In addition, the regression coefficient is positive, so it can be stated that the increase in toxic parenting causes an increase in bullying behavior.